Sintesis Dan Karakterisasi Hidroksiapatit Dari Cangkang Kerang Darah Dengan Proses Hidrotermal Variasi Suhu Dan pH - Bona Tua; Amun Amri; Zultiniar Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Hydroxyapatite (HAp) Ca10(PO4)6(OH)2 is a calcium phosphate compound which is bioactive ceramic material with high bioafinitas. It is one of bones and teeth constituent. In this research, HAp was synthesized by hydrothermal process with pH reaction of 8, 10, 12 and temperature reaction of 130, 150 and 170oC. Samples were characterized by Transform Infrared Spectroscopy (FTIR). The results of FTIR analysis revealed that synthesis of HAp with hydrothermal process showed the formation of hydroxyapatite with the presence of peaks PO43- and OH-. The best condition in this research at pH 12 with reaction temperature 170oC.Keywords: Blood cockle shell, characterization, hydroxyapatite, hydrothermal.